ORGANISATIONAL MODELS IN AGRICULTURE WITH SPECIAL REFERENCE TO SMALL FARMERS - Nebojša, Zakić; Svetlana, Vukotić; Cvijanović, Drago (Economics of Agriculture, 2014)
Agricultural value chains can be understood as the systems of people, organizations and activities needed to create process and deliver agricultural products from producers to consumers. Over time and due to huge changes that have happened in the surroundings, agricultural value chains have become very integrated and complex. Small farmers can prosper by joining in modern higher-level agricultural value chains, but there are numerous obstacles, as well. The work presents the typology of organizational models for agricultural production that consists of the models organised by producers, agribusiness companies (processors, retail chains, and intermediaries), facilitators (governments, non-governmental organisations) and completely integrated models, established by some big companies. None of these models provides ideal solutions from the perspective of small producers. However, they say that the institutions, such as cooperatives and small farmers’ organisations, present important mechanisms for including small producers in modern value chains and realizing the cooperation with agribusiness companies and other important players. This is also important for decision-makers and governmental bodies that should create a suitable environment and provide support so that small farmers and their organisations can integrate in modern value chains in a successful way.